Pengaruh Gaya Kepemimpinan Terhadap Kinerja Karyawan di Kelurahan Ujung Gurun - Wahyuni, Lidiya; Syamsir, Syamsir; Br Manurung, Isyka Ester Veronika; Maldini, Muhammad; Rezika, Mutiara (Inovan Publisher, 2025)
Every organization, whether public or private, has a leadership style that influences employee performance. A person's leadership style is a benchmark for their progress or decline in the organization they lead. One of the challenges faced by a leader is how to motivate employees to focus their abilities on the interests of the organization. The purpose of this study is to determine the influence of leadership style on employee performance in the Ujung Gurun sub-district and the obstacles and challenges faced by leaders in leading the Ujung Gurun sub-district. The research method used is a qualitative research method using a descriptive approach. This method describes or explains existing problems by providing answers to the problems raised. This research was conducted in the Ujung Gurun sub-district, Padang Barat district, Padang city, West Sumatra. In this study, the object of research was the head of the Ujung Gurun sub-district. The results of the study show that the leadership style applied in Ujung Gurun Village is a democratic leadership style, and the influence of this leadership style on employee performance is the extent to which leaders are able to embrace their members to achieve common goals and overcome the problems faced by their members.